Segmental ischemia and indocyanine green navigation: impact on perioperative parameters in laparoscopic vs. open partial nephrectomy - R.M. Molchanov; O.O. Honcharuk; G.G. Khareba; O.B. Blyuss; R.V. Duka (Medičnì Perspektivi)
The aim of this study is to compare perioperative parameters of laparoscopic partial nephrectomy and open partial nephrectomy in renal tumor management, and to evaluate the effect of using novel method of indocyanine green navigation in segmental ischemia on these parameters. The prospective study included 455 patients (89 laparoscopic partial nephrectomies, 366 open partial nephrectomies). Sub-groups (n=39, 32, 18) in Laparoscopic partial nephrectomy employed diverse ischemia techniques, including full warm ischemia, segmental ischemia with indocyanine green navigation and segmental ischemia without navigation. Parameters assessed encompassed estimated blood loss, operative time, warm ischemia time, and changes in estimated glomerular filtration rate. Covariate-balancing propensity scores ensured homogeneity. Statistical analysis included the Wilcoxon signed-rank test, for two matched groups. Two-sided p-values were reported for all statistical tests, a p-value <0.05 was considered to be statistically significant. The findings of the conducted research indicate that open partial nephrectomy has revealed significant differences in estimated blood loss, operative time, and warm ischemia time, in favor of open partial nephrectomy. Laparoscopic partial nephrectomy offers advantages in preserving renal function and minimizing estimated Glomerular Filtration Rate decline compared to open partial nephrectomy. The utilization indocyanine green navigation, facilitates precise and limited ischemia, contributing to enhanced preservation of renal function. Surgeons must weigh these considerations for optimal renal tumor management.